2001
DOI: 10.4141/s00-050
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nitrogen fertilizer requirements of potatoes in Atlantic Canada with soil nitrate determinations

Abstract: N. 2001. Predicting nitrogen fertilizer requirements of potatoes in Atlantic Canada with soil nitrate determinations. Can. J. Soil Sci. 81: 535-544. Nitrogen greatly affects potato (Solanum tuberosum L.) yield, but excess N can result in environmental degradation. In this study soil nitrate (NO 3 -N) content was determined pre-plant to predict fertilizer N requirements of potatoes in Atlantic Canada and in mid-season to adjust N fertilization during the growing season. Soil NO 3 -N contents were measured to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…3. This is consistent with previous reports of soil mineral N content in spring in potato fields (Bélanger et al 2001;. This suggests that soil N supply is controlled primarily by net soil N mineralization in most potato fields.…”
Section: Discussionsupporting
confidence: 93%
“…3. This is consistent with previous reports of soil mineral N content in spring in potato fields (Bélanger et al 2001;. This suggests that soil N supply is controlled primarily by net soil N mineralization in most potato fields.…”
Section: Discussionsupporting
confidence: 93%
“…MacLean and McRae (1987) found nitrification to be very sensitive to temperature, with nitrification of urea fertilizer N essentially complete after 48-68 d at 18°C, and 90% complete after 92 d at 9 and 13°C. The persistence of elevated NH 4 + -N concentrations for much of the growing season suggests that in-season sampling for soil inorganic N concentration, for example as suggested by Bélanger et al (2001), should be done for both NO 3 --N and NH 4 + -N. There was limited evidence of nitrate leaching during the growing season in this experiment. The only exception was evidence of downward movement of soil NO 3 --N within the hill observed at topkill in 1999 in response to the substantially above-average rainfall in September of 1999.…”
Section: Discussionmentioning
confidence: 78%
“…Milburn et al 1997) or soil inorganic N concentrations in potato fields at specific times (e.g. Bélanger et al 2001). However, no studies of soil N dynamics have been done in this region.…”
Section: Mots Clés: Solanum Tuberosum Nitrification Lixiviation Desmentioning
confidence: 99%
“…However, information on soil N dynamics in potato fields is limited, with most existing information coming from experimental plots (Bélanger et al 2001;Zebarth and Milburn 2003). Soil N processes are sensitive to soil and climatic conditions and to crop management practices.…”
mentioning
confidence: 99%
“…Spring soil inorganic N measurements have been used in making fertilizer N recommendations for potato in some potato production areas, for example in Germany (Wehrmann and Scharpf 1986). However, Bélanger et al (2001) concluded that preplant measurement of soil NO 3 content, or soil inorganic N content, did not adequately predict the optimal fertilizer N rate for potato in Atlantic Canada when used alone. This result is likely due in part to the greater importance of net soil N mineralization, compared to carry-over, in determining soil N supply in potato fields (Zebarth and Milburn 2003;Zebarth et al in prep.).…”
mentioning
confidence: 99%